A highly correlated topological index for polyacenes - Lakshmi, K Lavanya (Journal of Experimental Sciences, 2012)
The most used molecular graph descriptors in establishing Quantitative structure-property relationships (QSPRS) and Quantitative structure-activity relationships (QSARS) are topological indices. Molecular descriptors are normally chosen based on their ability to give good results in statistical models. In this paper we introduce a set of five new indices (Kekule indices) K, K1, K2, K3, K4 and we establish that the Kekule index (K) has excellent correlation (r = 0.99999997250969) with log p values in case of polyacenes.